Polyphenolic Profiling and Antioxidant Activity in Berry Extracts of Pyracantha Wild Varieties from the Mediterranean Region - Roberta Del Sole; Maria Assunta Montefusco; Raffaella Filippini; Lucia Mergola (MDPI AG, 2024)
Pyracantha is a genus of wild perennial shrubs native in an area extending from Southwest Europe to Southeast Asia, and it is used in traditional medicine for the diuretic, cardiac, and tonic properties of its fruits, which can also be cooked to make jellies, jams, and sauces. This work aims to study and compare the antioxidant activity and the phenolic and anthocyanin composition of three varieties of Pyracantha coccinea: Red Column (PCR), Orange Glow (PCO), and Soleil d'Or (PCS), and one of Pyracantha angustifolia: Orange glow (PAO), collected from the spontaneous flora of the Mediterranean region (Southern Italy). Two different extraction processes were tested using methanol and an aqueous methanol solution (80% MeOH) to evaluate the polyphenolic content and antioxidant activity of freeze-dried berries. The highest total phenolic content was found in PCR and PAO berries (174.21 ± 0.149 and 168.01 ± 0.691 mg of gallic acid equivalent per gram of dry matter, respectively) extracted with an aqueous methanol solution (80% MeOH). Polyphenolic extracts analyzed by HPLC-DAD-ESI/MS confirmed the presence of rutin, quercetin hexose, neoeriocitrin, procyanidin B, and resveratrol. Moreover, the total antioxidant activity of the berries' extracts was measured by comparing two different spectrophotometric methods (ABTS and DPPH), showing that the varieties with the highest total phenolic content, PCR and PAO, also had the highest scavenging activity. Finally, a suitable extraction process was chosen for the evaluation of the anthocyanins' composition of all frozen berries, and in all MS spectra of Pyracantha varieties, two ionic species at 449 m/z attributable to two cyanidin derivatives were found.